2008
DOI: 10.1007/s11596-008-0601-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and identification of scFv and bsFv against transferrin receptor

Abstract: To obtain single chain variable fragment (scFv) and bivalent single chain variable fragment (bsFv) against transferrin receptor, up-stream and down-stream primers were designed according to the complementary sequences of FR1 region of variable heavy (VH) and FR4 of variable light (VL), respectively, which contained inter-linker G4S and the restriction endonuclease SfiI, AscI and NotI. Two pieces of scFv fragments were first amplified through PCR and then inserted into plasmid pAB1, which could express scFv pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
(36 reference statements)
1
6
0
1
Order By: Relevance
“…We also found that the binding rate for the TfRscFv-GAL4 fusion protein with seven different tumor cell lines varied between 8.23% and 54.11%. The differences for the binding rate may account for TfR being found expressed preferentially in the proliferation or differentiation stage of these cells rather than G0 stage, which was consistent with the results from Crepin R et al [37] and our own results previously [12]. ELISA analysis indicated that the TfRscFv-GAL4 fusion protein can bind to anti-GAL4 antibody.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We also found that the binding rate for the TfRscFv-GAL4 fusion protein with seven different tumor cell lines varied between 8.23% and 54.11%. The differences for the binding rate may account for TfR being found expressed preferentially in the proliferation or differentiation stage of these cells rather than G0 stage, which was consistent with the results from Crepin R et al [37] and our own results previously [12]. ELISA analysis indicated that the TfRscFv-GAL4 fusion protein can bind to anti-GAL4 antibody.…”
Section: Discussionsupporting
confidence: 91%
“…A fragment for the TfRscFv cDNA was directly amplified by PCR using the amplimers 5'-CGGCCATGGCCCACGTTCAGCTGCAGCAGT-3' and 5'-GGCGGAATTCTTTGATTTCCAGCTTGGTC-3' from a pUC19 plasmid containing the TfRscFv sequence as described before [12]. The fragment for GAL4 was released from a pABgal4 plasmid (kindly provided by Dr. Bert W. O' Malley, Baylor College of Medicine, Houston, TX) by digestions of EcoRI and NotI restriction endonucleases (Thermo Scientific Fermentas).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations